Electron spin polarization in the triplet state of methoxy-substituted phosphorus(V) tetraphenyl porphyrins - D. Panariti; B.J. Bayard; A. Barbon; Y.E. Kandrashkin; P.K. Poddutoori; A. van der Est; M. Di Valentin (Journal of Magnetic Resonance Open)
Photoexcited triplet states of porphyrins are of great relevance in various applications due to their high yield, long lifetime, and strong electron spin polarization. This study delves into properties and spin dynamics of the triplet state of a series of hypervalent phosphorus(V) porphyrins. Transient Electron Paramagnetic Resonance (TrEPR) measurements, supported by quantum chemical calculations as well as by optical absorption/luminescence experiments, reveal that, unlike singlet states, the lowest triplet state does not exhibit charge-transfer (CT) character upon photoexcitation. However, the presence of excited CT singlet states alters the intersystem crossing in phosphorus(V) porphyrins, leading to a sign change in the initial multiplet polarization of the photoexcited triplet state. TrEPR results further demonstrate that significant net polarization develops in the triplet states of the phosphorus(V) porphyrins due to the dynamic Jahn-Teller effect. Yet, this effect remains largely unaffected by differences in their molecular structures.